A Comparison of Three Self-Report Pain Scales in Czech Patients with Stroke - Mandysová, Petra; Nedvědová, Adriana; Ehler, Edvard (My University, 2017)
The first aim was to determine the performance of three self-report pain scales, the combined Visual Analogue Scale / Numerical Rating Scale (VAS/NRS), NRS, and Faces Pain Scale – Revised (FPS-R), in a study on pain in Czech patients with stroke. The second aim was to compare the patients’ overall pain scale preference rankings and preference rankings by gender, the location of the brain damage, and cognitive functioning. Design: The design was cross-sectional. Methods: Eighty hospitalized patients with stroke evaluated their pain using the mentioned scales and subsequently expressed their preference rankings of the scales. The data were described and analysed using descriptive and inferential statistics. Results: Nineteen (24%) patients reported pain using at least one scale. Overall, pain intensity scores varied by 0–1 point in 75 (93.8%) patients, and the highest Spearman correlation was 0.997 (p < 0.001) between the VAS/NRS and the NRS. Overall, the NRS had the highest preference ranking (it ranked first or second in 75% of the cases). Conclusion: Correlations across all three scales were moderate to high; therefore, they appear equivalent. The scales can be recommended for clinical use in stroke patients provided they are able to collaborate.
Porovnání tří sebehodnotících škál bolesti u českých pacientů s cévní mozkovou příhodou
Keywords: stroke; pain scale; Faces Pain Scale – Revised; Numerical Rating Scale; Visual Analogue Scale; cévní mozková příhoda; Faces Pain Scale – Revised; vizuální analogová škála; numerická škála